Pengolahan Sampah Plastik Berbasis Partisipasi Masyarakat di Desa Krompaan Kecamatan Gemuh Kabupaten Kendal - Annurroin, Nur Muhammad; Wibowo, Wisnu; Mufidah, Nurul; Kamila, Nur; Fuad, Anas; Shabila, Shasa; Munandar, Yusuf; Fuadi, Azmi; Malikha, Nada Khamilia; Sufa, Afni Laila; Dewi, Farihal Husna; Nisa, Soimatun; Nada, M. Faza Bida; Mutohar, Fatih (LPPM Sekolah Tinggi Islam Kendal, 2026)
Plastic waste in rural areas has become an increasingly complex environmental issue due to the rising volume of household waste and the lack of effective waste management systems based on source reduction. This community service program aims to enhance public awareness and participation in plastic waste management through a community-based approach in Krompaan Village, Gemuh District, Kendal Regency. The implementation method employed a participatory approach consisting of three stages: preparation, implementation, and evaluation. The implementation stage included socialization, environmental education, assistance in waste segregation, and the introduction of the reduce, reuse, and recycle (3R) concept, as well as the initiation of a waste bank. The results indicate an improvement in community understanding regarding the impact of plastic waste and the importance of managing waste at the source. Community participation began to emerge through involvement in socialization activities and initial practices of waste segregation, although it has not yet been consistently applied in daily life. The program also identified potential for developing community-based waste management supported by social capital and the role of local government. Therefore, this community service activity provides an initial contribution to fostering awareness and participation toward a more participatory and sustainable plastic waste management system.